PENINGKATAN PENDAPATAN PETERNAK KAMBING MELALUI OPTIMALISASI MANAJEMEN PEMELIHARAAN DI KECAMATAN PATTALLASSANG KABUPATEN GOWA - Ilma Wulansari Hasdiansa; Sitti Hasbiah; Annisa Paramaswary Aslam; Nurul Fadilah Aswar; Andi Dewi Angreyani (Lafadz Jaya Publisher, 2026)
This community service activity aims to improve the capacity of goat farmers by optimizing livestock management in Sanging-Sanging Village, Pattallassang District, Gowa Regency. The main challenges faced by the partners included limited knowledge of feed management, suboptimal housing systems, and a lack of understanding of livestock health. The activity was conducted in February 2026 and involved five small-to-medium-scale goat farmers, each with between 40 and 100 goats. The methods used included observation, counseling, training, and participatory mentoring. The results showed an increase in farmers' knowledge and skills in feed management, improved housing systems, and the implementation of better husbandry practices. Farmers began implementing more regular feeding, maintaining clean pens, and utilizing livestock waste as organic fertilizer. Furthermore, there was an increase in farmers' awareness of the importance of more efficient business management. Although income increases were not yet significant in the short term, there were indications of improved business efficiency, which has the potential to increase profits in the long term. This activity demonstrated that the counseling and mentoring approach is effective in increasing farmer capacity and supporting the development of goat farming businesses at the community level.